Estimation of Wind Effects on High-Rise Structures by the Global Load Effects and Database-Assisted Design Methods - Simiu, Emil (International Journal of Architectural Engineering Technology, 2025)
Structural wind effects on high-rise buildings subjected to extreme directional winds can be determined by one of three methods: (i) HFB (high frequency balance), used only for buildings with very complex shapes or with many fine-scale features, (ii) GLE (global load effects), commonly used in current commercial wind engineering laboratory practice, and (iii) the DAD (Database Assisted Design) method. The purpose of this paper is to consider the advantages and drawbacks of the GLE and DAD methods, both of which use the multi-channel pressure scanning system. Following these methods’ brief description, it is noted that the GLE method has over DAD the advantage of significantly lower computational time requirements. This is shown to be due to GLE’s basic assumption that the peak Demand-to-Capacity Indexes (DCIs) of all the building’s structural members occur at the same time. It is then shown that this assumption is incorrect, and that it results in the GLE method’s underestimation of all the structural members’ DCIs, inter-story drift ratios, and top floor accelerations. In contrast, the DAD method is shown to satisfy all applicable strength and serviceability performance criteria. However, the computational resources required for DAD’s use exceed the resources typically available to small or mid-sized structural design offices. Recent research results concerning the DAD method are then noted, and various approaches are proposed to the reduction of the DAD method’s computation time requirements by up to two orders of magnitude.